2021
DOI: 10.3390/drones5010013
|View full text |Cite
|
Sign up to set email alerts
|

A Quickly Deployed and UAS-Based Logistics Network for Delivery of Critical Medical Goods during Healthcare System Stress Periods: A Real Use Case in Valencia (Spain)

Abstract: On the one hand, Unmanned Aircraft Systems (UASs) have experienced great applicability surge in the recent years, arising as a promising technology with a wide field of use. On the other hand, healthcare, a critical system in modern society, is subject to a heavy and unexpected pressure in the case of situations such as the COVID-19 pandemic. This article aims to leverage the flexibility of UASs as complementary support for healthcare logistic systems when under high-stress conditions, via quick deployment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…There are also no reports on the visual transport of heavy medicines using the multi-copter. For example, Garcia IQ et al reported excellent results with the Matrix 300 RTK, which is a multi-copter [19]. However, the Matrix 300 RTK cannot transport heavy-weight objects.…”
Section: Discussionmentioning
confidence: 99%
“…There are also no reports on the visual transport of heavy medicines using the multi-copter. For example, Garcia IQ et al reported excellent results with the Matrix 300 RTK, which is a multi-copter [19]. However, the Matrix 300 RTK cannot transport heavy-weight objects.…”
Section: Discussionmentioning
confidence: 99%
“…However, the transport capacity of the DJI MARICE 300 RTK used for this purpose is approximately 2 kg. 13 We aimed to transport blood in a temperaturecontrolled environment, and the M1000 permitted load of 24.9 kg, which means that it can carry a load of more than 10 kg after subtracting its own weight. However, for safety reasons, drones such as M1000 are too large for practical use.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared with physical movement, Simic et al (2021) specifically analyzed the Belgrade region when determining the optimal last‐mile distribution (LMD) mode, and determined that postal transport was the best mode of transport for LMD, followed by cargo bikes, drones, conventional couriers, self‐driving cars, and metro transport. Quintanilla Garcia et al (2021) also stated that drones are primarily concerned with control link quality and air traffic management (ATM) integration. It can be concluded that the deployment of drones as part of a logistical network is a viable method of assisting existing infrastructure, particularly in times of extreme need.…”
Section: Impacts Of Covid‐19 On Logistics In Various Fieldsmentioning
confidence: 99%